Sexual size dimorphism and sexual selection in artiodactyls. (29th March 2020) - Cassini, Marcelo H
Abstract: Sexual size dimorphism is biased toward males in most mammalian species. The most common explanation is precopulatory intramale sexual selection. Large males win fights and mate more frequently. In artiodactyls, previous tests of this hypothesis consisted of interspecific correlations of sexual dimorphism with group size as a surrogate for the intensity of sexual selection ( I s ). However, group size is not a proper measure of sexual selection for several reasons as is largely recognized in other mammalian taxa. I conducted an interspecific test on the role of sexual selection in the evolution of sexual dimorphism using the variance in genetic paternity as a proxy for the I s . I reviewed the literature and found 17 studies that allowed estimating I s = V /( W 2 ), where V and W are the variance and mean number of offspring per male, respectively. A phylogenetic generalized least squares analysis indicated that dimorphism ( W m / W f ) showed a significant positive regression with the intensity of sexual selection but not group size (multiple r 2 = 0.40; F 3, 17 = 12.78, P = 0.002). This result suggests that sexual selection may have played a role in the evolution of sexual size dimorphism in Artiodactyla. An alternative hypothesis based on natural selection is discussed. Abstract : In most animals, females are larger than males. Paradoxically, sexual size dimorphism is biased toward males in most mammalian species. An accepted explanation is that sexual dimorphism in mammals evolved by intramale sexual selection. I tested this hypothesis by correlating sexual dimorphism with male reproductive success—measured using genetic paternity—in different Artiodactyl species. I found support for the sexual selection hypothesis; however, I also propose an alternative explanation based on natural selection.